Multifunctional cell membranes-based nano-carriers for targeted therapies: a review of recent trends and future perspective - Mo Li; Qiushi Guo; Chongli Zhong; Ziyan Zhang (Taylor & Francis Group, 2023)
AbstractNanotechnology has ignited a transformative revolution in disease detection, prevention, management, and treatment. Central to this paradigm shift is the innovative realm of cell membrane-based nanocarriers, a burgeoning class of biomimetic nanoparticles (NPs) that redefine the boundaries of biomedical applications. These remarkable nanocarriers, designed through a top-down approach, harness the intrinsic properties of cell-derived materials as their fundamental building blocks. Through shrouding themselves in natural cell membranes, these nanocarriers extend their circulation longevity and empower themselves to intricately navigate and modulate the multifaceted microenvironments associated with various diseases. This comprehensive review provides a panoramic view of recent breakthroughs in biomimetic nanomaterials, emphasizing their diverse applications in cancer treatment, cardiovascular therapy, viral infections, COVID-19 management, and autoimmune diseases. In this exposition, we deliver a concise yet illuminating overview of the distinctive properties underpinning biomimetic nanomaterials, elucidating their pivotal role in biomedical innovation. We subsequently delve into the exceptional advantages these nanomaterials offer, shedding light on the unique attributes that position them at the forefront of cutting-edge research. Moreover, we briefly explore the intricate synthesis processes employed in creating these biomimetic nanocarriers, shedding light on the methodologies that drive their development.